An Assessment of Pain Management Among Patients Presenting to Emergency Medical Services After Suffering a Fall. Issue 4 (19th June 2014) - Infinger, Allison E.; Studnek, Jonathan R.
Abstract Introduction Emergency Medical Services (EMS) professionals frequently care for patients experiencing acute pain. Analgesics are critical in patient comfort and satisfaction levels during the treatment of acute pain. The objective of this study was to assess the frequency of pain management in patients suffering a fall, the documented pain score, and the location of their injuries. It was hypothesized that the frequency of analgesia administration was low and would be associated with injury location. Methods This was a retrospective review of patients presenting with a complaint of an injury from a fall transported by a single municipal EMS system. Administration of analgesia was the primary outcome variable, with pain severity, injury location, age, gender, race, and distance of fall the independent variables of interest. Pain severity was assessed using a 0-10 scale. Injury location was defined as head/neck, extremities, back, and hip. Patients were deemed ineligible for analgesia, according to local protocol, if they reported chest or abdominal pain, or were hemodynamically unstable as determined by an assessment of pulse and blood pressure. Results There were 1, 200 patients who were classified as having injuries suffered from a fall, with 76 (6.3%) ineligible for analgesia. Ninety-two (8.2%) patients received analgesia, and they had a mean recorded pain score of 9.1 (95% CI, 8.7-9.5), which was higher than those who did not receive analgesia (5.8; 95% CI, 5.5-6.2). Analgesia administration was associated with injury location; patients experiencing an extremity injury (OR = 13.23; 95% CI, 5.58-31.36; P < .001) or hip injury (OR = 11.65; 95% CI, 4.64-29.24; P < .001) had increased odds of analgesia administration compared to those with head/neck injury. The odds of analgesia administration were decreased for black patients (OR = 0.19; 95% CI, 0.08-0.44; P < .001) when compared to white patients. Conclusion Analgesia administration was provided to 10% of eligible patients, and was associated with injury location. Of concern was the number of patients who suffered a fall and did not receive a documented pain score. The results from this study indicated a need for education relating to pain management in patients suffering a fall. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>AE</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Infinger</surname> </string-name>, <string-name><given-names>JR</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Studnek</surname></string-name>. An assessment of pain management among patients presenting to Emergency Medical Services after suffering a fall . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>4</issue>):<fpage>1</fpage>-<lpage>6</lpage>.</mixed-citation>